Amazônia INC. : sociedades anônimas da Amazônia - Bogado, Sabrina (Levante Filmes : Sagui films, 2017)
The forest peoples, the "anonymous" and forgotten societies of the Amazon, are having to organize themselves and form legal entities to confront the big corporations that, with the support of the government, invade their territories.